POLA PEMBAGIAN HUKUM KEWARISAN ISLAM BAGI ANAK LAKI-LAKI DAN ANAK PEREMPUAN - Noor, Muhammad (IAIN Samarinda, 2012)
The pattern of distribution of the provisions of Islamic inheritance law with Islamic law excavation methodology can be aligned with the values of justice is perceived and lived in public life. Formulation of new laws that are relevant to the needs of people who experience social change, so that the Islamic inheritance law that is universal will be passed on without knowing the limits of territorial and social environment. The result of Islamic inheritance law will have the flexibility and power with good adaptability to changes in society. Reformulation of the law as a result of changes in running condition by reconstructing relationships within the community. This means that the cause of law are closely related and should be able to anticipate changes in society, because that law is required to formalize the relationship between community members.